Short-term response of fish assemblages to instream habitat restoration in heavily impacted streams - Manzotti, Angelo Rodrigo [UNESP] (2020)
Habitat homogenization has been a major impact in stream ecosystems, and it is considered one of the main drivers of biotic homogenization as well, leading to the loss of water quality and fish diversity. In this study, we added artificial woody structures and leaf packs in physically impacted streams to test if the additions can improve habitat complexity and change the taxonomic and functional structure of fish communities. The experiment was done in eight streams impacted by siltation, deforestation, and habitat homogenization, inserted in an agricultural landscape from the Upper Paraná River Basin, and lasted 112 days. The provision of artificial microhabitats increased instream habitat diversity by creating patches of organic matter deposits, changing flow, and providing substrate for grass colonization of the instream habitat. The experimental manipulation also changed fish species abundance. Nine species contributed to these changes, five decreased and four increased in abundance, indicating species responded differently to the experimental manipulation. However, overall species richness, diversity, and community functional traits remained unaltered. These results indicate that short-term habitat restoration on a local scale may not be enough to promote changes in fish community attributes of streams that are heavily impacted.